Perceived Risk Associated with Technology Adaptation in Nepal and the Role of Government Policies in Mitigating Risks and Building Trust (Victoria Journal of Management, 2025)
This study investigates the influence of perceived risk and government policies on the adoption of mobile financial services (MFS) in Nepal. While financial risk negatively affects adoption, government policies positively influence consumer intention to use MFS. Perceived risk shows a negative correlation with adoption but does not significantly affect behavioural intentions, potentially due to respondents’ dual roles as users and employees of MFS providers. Confidence in MFS is bolstered by advanced customer support and automatic refund mechanisms. Government policies play a pivotal role in driving MFS adoption, as proactive regulation fosters development, enhances consumer trust, and ensures the reliability of financial services. Overcoming perceived risk barriers remains essential for building trust in new technology and facilitating its seamless adaptation.